(untitled) (Boletín Semillero de Investigación en Familia, 2023)
Introduction: with the implementation of social projects, the Facultad de Ciencias de la Salud de la Universidad de los Llanos seeks to help improve the quality of health institutions with which the institution has a teaching and service agreement, by means of of continuing education, structuring courses that allow strengthening human talent in health after graduation, responding to the needs for updating in line with current regulations. Objective: to strengthen the professional skills of graduates of the Facultad de Ciencias de la Salud de la Universidad de los Llanos through their participation in continuous training processes of a social nature. Materials and methods: a form was designed and the courses to be offered were prioritized. Lastly, it supported the creation of thematic content for each of the courses. Results: the design and four continuing education courses were offered. I obtained an outstanding evaluation, in the five items of the satisfaction survey. Conclusion: the continuing education courses had an impact on the training of human talent and the social responsibility of the Universidad de los Llanos.